What Is New in the Pathologic Staging of Penile Carcinoma in the 8th Edition of AJCC TNM Model: Rationale for Changes With Practical Stage-by-stage Category Diagnostic Considerations. (27th July 2021) - Sanchez, Diego F.; Fernandez-Nestosa, Maria Jose; Canete-Portillo, Sofia; Rodriguez, Ingrid; Cubilla, Antonio L.
Abstract : For >50 years the tumor, node, metastasis (TNM) classification model of malignant tumors has been the main resource for clinicians, pathologists, radiologists and public health professionals ensuring a homogeneous classification and patients' management based on common staging and prognosis factors. Penile cancer was first included for staging in the third edition of the TNM classification with several changes in the last version, the 8th edition of the AJCC TNM Manual, in 2017. Some changes in the pT category were done due to recent knowledge regarding the prognostic importance of anatomical level of invasion, vascular and perineural invasion and tumor grading. These changes must be interpreted in the light of a required understanding of the complex anatomy of penile compartments especially their histological boundaries, the morphological differences of each level needed for the correct classification, the heterogeneity of penile squamous cell carcinomas and an adequate criticism of the current model used by the TNM system. We present here a series of stage-by-stage category diagnostic considerations based on the clinical experience acummulated over the years of applying the different TNM staging classifications in our large clinical practice. Some discrepancies will need well-designed prospective studies for im4proving the actual classification.